Evaluation of antidiabetic activity of kaempferol isolated from Cardiospermum Halicacabum leaf extract in alloxan induced diabetic rats - R. RAJESWARI (International Journal of Pharma and Bio Sciences, 2019)
Diabetes mellitus is the most common non-communicable disease worldwide with the highest rates of prevalence and mortality. No satisfactory therapy still achieved by modern medicines in the treatment of Diabetes because of its side effects. Drugs isolated from medicinal plants showed effective antidiabetic activity than oral hypoglycemic drugs. Cardiospermum halicacabum is an herbaceous climber used for several centuries in the treatment of various ailments. Although the hypoglycaemic effect of this plant has been reported, still there is no report of isolated compounds for the same. The purpose of the present study is to evaluate the in vivo antidiabetic activity of isolated compound from Cardiospermum halicacabum. Eleven compounds have been isolated from the hydroalcoholic leaf extract of Cardiospermum halicacabumthrough Column Chromatography and Thin Layer Chromatography based on standard bioassay guided isolation procedure. Preliminary in vitro analysis were done with the eleven compounds, amongst Kaempferol showed enhanced in vitro activities. Kaempferol, a natural polyphenol belonging to the flavonoid group identified in many plant species has a wide range of pharmacological activities. Hence in this study, the hypoglycemic effect of kaempferol isolated from Cardiospermum halicacabum has been evaluated in diabetic animal model. Kaempferol comparatively lowers blood glucose level than standard oral hypoglycemic drugs in rat models. Oral administration of kaempferol showed significant inflection in carbohydrate metabolic enzyme levels, improvement in Hb and insulin level reduction in HbA1c level. Histopathological studies of pancreas showed the regeneration of βâ€cells of Kaempferol treated animals, which positively correlateds with blood glucose level So from the results obtained it can be concluded as Cardiospermum halicacabum definitely be suggested in regular diet for Diabetic patients and also kaempferol will be helpful in the formulation of new hypoglycemic drugs in future.